Odpowiedź :
D=R/{-1,0,1}, bo x²≠x
(2/x²-x)-(3/x²+x)= (sprowadzamy do wspólnego mianownika)
2(x²+x)/(x²-x)(x²+x)-3(x²-x)/(x²+x)(x²-x)=
2x²+2x-3x²-3x/(x²-x)(x²+x)= (redukcja wyrazów podobnych)
-x²-x/(x²-x)(x²+x)=
-1(x²+x)/(x²-x)(x²+x)=(skracamy)
-1/x²-x
(2/x²-x)-(3/x²+x)= (sprowadzamy do wspólnego mianownika)
2(x²+x)/(x²-x)(x²+x)-3(x²-x)/(x²+x)(x²-x)=
2x²+2x-3x²-3x/(x²-x)(x²+x)= (redukcja wyrazów podobnych)
-x²-x/(x²-x)(x²+x)=
-1(x²+x)/(x²-x)(x²+x)=(skracamy)
-1/x²-x
dziedzina x²≠0 czyli x≠0
(2/x²-x)-(3/x²+x) =2/x²-x-3/x²-x=-1/x² -2x
pozdrowienia
(2/x²-x)-(3/x²+x) =2/x²-x-3/x²-x=-1/x² -2x
pozdrowienia